2018
DOI: 10.1161/circinterventions.118.007145
|View full text |Cite
|
Sign up to set email alerts
|

Surgical Atrioventricular Valve Replacement With Melody Valve in Infants and Children

Abstract: Background Pediatric patients with atrioventricular valve disease have limited options for prosthetic valve replacement in sizes <15 mm. Based on successful experience with the stented bovine jugular vein graft (Melody valve) in the right ventricular outflow tract, the prosthesis has been modified for surgical valve replacement in pediatric patients with atrioventricular dysfunction with the intention of subsequent valve expansion in the catheterization laboratory as the child grows. Methods and Results A mult… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
57
2

Year Published

2019
2019
2023
2023

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 74 publications
(60 citation statements)
references
References 32 publications
1
57
2
Order By: Relevance
“…There are case reports of successfully performed mitral valve replacement from 6 months of age7 8 and mitral valve repair from teenage years 9 15. Recently Pluchinotta et al 16 reported a multicentre study of surgical implantation of the Melody bioprosthetic valve in mitral position for children and infants with intractable mitral disease as early as the neonatal period. The median age and weight at implantation was 8.6 months (range 3 days to 14 years) and 6.6 kg (range not reported), respectively 16.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…There are case reports of successfully performed mitral valve replacement from 6 months of age7 8 and mitral valve repair from teenage years 9 15. Recently Pluchinotta et al 16 reported a multicentre study of surgical implantation of the Melody bioprosthetic valve in mitral position for children and infants with intractable mitral disease as early as the neonatal period. The median age and weight at implantation was 8.6 months (range 3 days to 14 years) and 6.6 kg (range not reported), respectively 16.…”
Section: Discussionmentioning
confidence: 99%
“…Recently Pluchinotta et al 16 reported a multicentre study of surgical implantation of the Melody bioprosthetic valve in mitral position for children and infants with intractable mitral disease as early as the neonatal period. The median age and weight at implantation was 8.6 months (range 3 days to 14 years) and 6.6 kg (range not reported), respectively 16. The experience with this technique is still very limited, and in a preterm neonate weighing only 2 kg there would probably be only a minimal chance ofgain 16…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…There are reports and case series of its use in mitral or tricuspid position. [1][2][3][4][5] The valve diameter is determined by the stent. An increasing gradient over the valve maybe an indication for re-intervention.…”
Section: Introductionmentioning
confidence: 99%
“…An increasing gradient over the valve maybe an indication for re-intervention. 1,2,4,5 Case report A non-syndromatic baby with AV septal defect was operated at the age of 6 weeks with a weight of 3.5 kg as she showed progressive signs of heart failure. Repair of the left AV valve was difficult due to the lack of tissue, and the child showed severe left AV valve insufficiency post-operatively.…”
Section: Introductionmentioning
confidence: 99%